2010
DOI: 10.1037/a0019859
|View full text |Cite
|
Sign up to set email alerts
|

Early attentional deficits in an attention-to-prepulse paradigm in ADHD adults.

Abstract: Adults with attention-deficit/hyperactivity disorder (ADHD) were examined for early and late attentional processes as a function of controlled attention. The test paradigm was the attentional modulation of prepulse inhibition (PPI; early controlled attentional processing) and prepulse facilitation (PPF; late controlled attentional processing). In 49 patients and 49 controls, the authors measured acoustic startle responses to 96-dB startle pulses preceded 120, 240 (for PPI), 2,000, and 4,500 (for PPF) ms by a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Prior work has indicated that the experience of positive emotion is highly correlated with proper functioning in cognitive, affective and social domains (Fredrickson, 2001;Fredrickson et al, 2008). Furthermore, maladaptive positive emotional responses have been associated with psychological disorders like substance abuse (Winkler et al, 2011;Geier et al, 2000), depression (Aldao et al, 2010) and ADHD (Conzelmann et al, 2010;Conzelmann et al, 2011). Hence, further studies that investigate the impact of appraisal frames on emotional responses to pleasant stimuli would not only extend prior work, but may also have important implications for cognitive psychotherapy.…”
Section: Introductionmentioning
confidence: 93%
“…Prior work has indicated that the experience of positive emotion is highly correlated with proper functioning in cognitive, affective and social domains (Fredrickson, 2001;Fredrickson et al, 2008). Furthermore, maladaptive positive emotional responses have been associated with psychological disorders like substance abuse (Winkler et al, 2011;Geier et al, 2000), depression (Aldao et al, 2010) and ADHD (Conzelmann et al, 2010;Conzelmann et al, 2011). Hence, further studies that investigate the impact of appraisal frames on emotional responses to pleasant stimuli would not only extend prior work, but may also have important implications for cognitive psychotherapy.…”
Section: Introductionmentioning
confidence: 93%
“…Swerdlow and Koob, 1987). However, it is also critical to note that PPI (and presumably its underlying neural regulation) appears to remain relatively intact, or at least functional, in a number of other serious brain disorders, including attention deficit disorder (ADHD; Castellanos et al, 1996; Conzelmann et al, 2010; Feifel et al, 2009; Hanlon et al, 2012; Ornitz et al, 1992, 1999), high functioning autism (Kohl et al 2014), bipolar disorder (in euthymic states; Barrett et al, 2005; Carroll et al, 2007; but see Sanchez-Morla et al, 2016), and major depressive disorder (Ludewig and Ludewig, 2003; Perry et al, 2004; Quednow et al, 2006), while evidence from chronic substance use disorders is mixed and likely to be substance specific (e.g. Quednow et al, 2004; Schellekens et al, 2012).…”
Section: Theme 1: Ppi Is Impaired Across Categorically Distinct Neuromentioning
confidence: 99%
“…ADHD is behaviorally identified as developmentally inappropriate levels of impulsive actions (e.g., trouble waiting turns and interrupting others), hyperactivity (e.g., fidgety), and inattention (e.g., difficulty focusing, distractibility, and forgetfulness) (DSM-IVTR; APA, 2000). Empirically, ADHD is associated with impaired response inhibition (Hervey et al 2004; Lijffijt et al 2005), interference control (Conzelmann et al 2010; Hawk et al 2003), and greater delay discounting (Barkley et al 2001). The strong association between smoking and ADHD has led some to suggest that individuals with ADHD smoke to self-medicate symptoms of inattention and impulsivity.…”
Section: Introductionmentioning
confidence: 99%